India's first dictatorship : the emergency, 1975 -1977 - Jaffrelot, Christophe; Anil, Pratinav (Noida HarperCollins, 2021)
In June 1975 Prime Minister Indira Gandhi imposed a state of emergency, resulting in a 21-month suspension of democracy across India. Christophe Jaffrelot and Pratinav Anil explore this black page in India's history, a constitutional dictatorship of unequal impact, with South India largely spared thanks to the resilience of Indian federalism.
Keywords: Politics and government